NGS targeted screening of 100 Scandinavian patients with coronal synostosis. Issue 2 (14th December 2019) - Topa, Alexandra; Rohlin, Anna; Andersson, Mattias K.; Fehr, André; Lovmar, Lovisa; Stenman, Göran; Kölby, Lars
Abstract: Craniosynostosis (CS), the premature closure of one or more cranial sutures, occurs both as part of a syndrome or in isolation (nonsyndromic form). Here, we have studied the prevalence and spectrum of genetic alterations associated with coronal suture closure in 100 Scandinavian patients treated at a single craniofacial unit. All patients were phenotypically assessed and analyzed with a custom‐designed 63 gene NGS‐panel. Most cases (78%) were syndromic forms of CS. Pathogenic and likely pathogenic variants explaining the phenotype were found in 80% of the families with syndromic CS and in 14% of those with nonsyndromic CS. Sixty‐five percent of the families had mutations in the CS core genes FGFR2, TWIST1, FGFR3, TCF12, EFNB1, FGFR1, and POR . Five novel pathogenic/likely pathogenic variants in TWIST1, TCF12, and EFNB1 were identified. We also found novel variants in SPECC1L, IGF1R, and CYP26B1 with a possible modulator phenotypic effect. Our findings demonstrate that NGS targeted sequencing is a powerful tool to detect pathogenic mutations in patients with coronal CS and further emphasize the importance of thorough assessment of the patient's phenotype for reliable interpretation of the molecular findings. This is particularly important in patients with complex phenotypes and rare forms of CS.